Paragraph Shrinking Strategy for Teaching Reading Nursing Student - Wildan, Asef; Zainudin, Moh; Merbawani, Raras (Kirana Publisher (KNPub), 2022)
The goal of this study is to determine whether or not the paragraph-shrinking strategy significantly affected students' reading comprehension. This study used an experimental design with a posttest-only control group. The control class received treatment using the usual technique, while the experimental class received treatment using the paragraph shrinking strategy. This study used a multiple-choice reading test as its instrument. This instrument was valid because it was based on the syllabus and had subject validity that had been taught in the past. Because the writer had tested the instrument and divided the reliability in half, it was then reliable. After that, the writer utilized Gay's suggested t-test procedure to examine the data and determine whether the hypothesis was correct.